2021
DOI: 10.3390/atmos12081042
|View full text |Cite
|
Sign up to set email alerts
|

The Unmanned Systems Research Laboratory (USRL): A New Facility for UAV-Based Atmospheric Observations

Abstract: The Unmanned Systems Research Laboratory (USRL) of the Cyprus Institute is a new mobile exploratory platform of the EU Research Infrastructure Aerosol, Clouds and Trace Gases Research InfraStructure (ACTRIS). USRL offers exclusive Unmanned Aerial Vehicle (UAV)-sensor solutions that can be deployed anywhere in Europe and beyond, e.g., during intensive field campaigns through a transnational access scheme in compliance with the drone regulation set by the European Union Aviation Safety Agency (EASA) for the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Renard et al (2018) frequently observed particles sized larger than 40 μm at concentrations above 10 -4 cm -3 at a distance from source regions. Other instruments, such as the Universal Cloud and Aerosol Sounding System (UCASS, Smith et al, 2019), a lightweight OPC which can be deployed on radiosondes, dropsondes or UAVs to measure size distributions between optical diameters between 0.4 to 17 μm have also been developed and show promising results (Kezoudi et al, 2021a(Kezoudi et al, , 2021b.…”
Section: Observations From Unmanned Aerial Vehicles Radiosondes and F...mentioning
confidence: 99%
“…Renard et al (2018) frequently observed particles sized larger than 40 μm at concentrations above 10 -4 cm -3 at a distance from source regions. Other instruments, such as the Universal Cloud and Aerosol Sounding System (UCASS, Smith et al, 2019), a lightweight OPC which can be deployed on radiosondes, dropsondes or UAVs to measure size distributions between optical diameters between 0.4 to 17 μm have also been developed and show promising results (Kezoudi et al, 2021a(Kezoudi et al, , 2021b.…”
Section: Observations From Unmanned Aerial Vehicles Radiosondes and F...mentioning
confidence: 99%
“…POPS uses a 405 nm diode laser and measures aerosol number concentration in the diameter range from 0.14 to 3 µm. A dryer is attached to the inlet of the instrument when the UAV-POPS system flies inside humid environments (with RH > 50%) [8]. Compared with reference instruments, groundbased and UAV observations of POPS have shown that POPS can provide scientific quality data and reliable vertical profiles of particle size distribution and mass concentration [9].…”
Section: Popsmentioning
confidence: 99%
“…A potential solution for filling this observational gap is the development of Lower-Cost Medium Precision (LCMP) instruments, as the zenith looking narrow-band radiometer (Almansa et al 2017(Almansa et al , 2020, with no mobile parts, specifically designed to measure desert dust, and land low-cost sensors operated by national weather services or even transportable on unmanned vehicles or drones (e.g., Morys et al 2001;Guirado et al 2014; http://www. calitoo.fr; Pikridas et al 2019;Kezoudi et al 2021). These instruments could benefit from more advanced instrumentation for testing, validation, and quality assessment (Giordano et al 2021).…”
Section: The Way Forward: Gaps and Recommendationsmentioning
confidence: 99%